Digital Sunspot Counting For Langkawi National Observatory In White Light Full Disk - Kamarudin, Farahana (2018)
For over 400 years, sunspot observation has been consistently collected and it has become the longest-running experiment and still ongoing scientific project. Sunspot numbers are manually counted based on direct visual observation or drawing it through the projection method. Langkawi National Observatory (LNO) has carried out consistent sunspot observation since 2008. LNO is equipped with CCDs and capable of recording sunspot in the form of digital images. From these images, the numbers of sunspots are manually counted by observers to get LNO’s daily RSN. Bias from different observers and weather factor like haze or thin cloud cover leads to inconsistency due to different individual visual characteristics.